Reassessing evidence: a new proposal for the dating of the theatre of Segesta - Panagiotonakou, Maria (Journal of Greek Archaeology, 2023)
The theatre of Segesta is perhaps the most well-studied example in Sicily after the theatre of Syracuse. It belongs in the group of theatres with a paraskenia scene building, just as the theatres of Tyndaris, Solous and Iaitas. Due to the lack of solid archaeological evidence and its fragmentary nature, our understanding of the architectural evolution of these monuments over time has been limited. The issue of dating in particular is related to the issue of the Romanization of Sicily and has caused a clash of viewpoints among researchers who place their initial construction from the mid-4th century to the end of the 2nd century BC. The main reason for this is that modern scholarship has been, and remains, deeply divided over the economic, demographic, social and cultural impact of the imposition of Roman rule on Sicily. Significant advances in historical and archaeological research on Hellenistic Sicily, though, offer arguments for the formation of a fresh interpretative framework. The present study will focus on the theatre of the Elymian city of Segesta. After a short discussion of its archaeological exploration, the architecture of the monument and scholars’ views on the issue of dating will be addressed. Through the re-evaluation of the results of recent studies, their comparison and synthesis with the results of older excavations, and by drawing upon archaeological, and historical evidence, this paper seeks to further elucidate the complex political, social, and economic forces that contributed to the architectural evolution of the theatre of Segesta and to integrate it into a more specific cultural and chronological context.